Frequency and clinical characteristics of HER2 over-expressed breast cancer in Saudi Arabia: a retrospective study - Jamal Zekri; Ahmed Saadeddin; Hulayel Alharbi (BMC, 2021)
Abstract Introduction This study aimed to determine the frequency of human epidermal growth factor receptor 2 (HER2) over-expression in newly diagnosed breast cancer (BC) patients in Saudi Arabia and to assess the clinical characteristics and outcomes in patients with HER2-positive disease. Methods In the first part of the study, we retrospectively reviewed the pathology records of all patients diagnosed with BC between 2007 and 2013 at 3 hospitals in the largest 3 cities in Saudi Arabia to determine the frequency of HER2 over-expression. In the second part, a representative sample from the patients identified with HER2 over-expressed BC was selected for further investigation. Data collected included demographic and clinical characteristics such as hormone-receptor status, treatment regimens, survival data, response to treatment, and selected adverse events. Results 1867 BC records were included in the study. HER2 was overexpressed in 559 patients (29.9%); of those, 348 HER2-positive BC patients were included in subsequent analyses. In the sample of HER2-positive BC patients, median age at diagnosis was 46 years, 0.9% were male, 92.5% were Saudi, 42.4% were Hormone Receptor-negative, and 13.1% had stage IV tumors. Most patients (84.2%) underwent curative intent surgery and 71.8% received radiotherapy. Average tumor size was 3.5 ± 2.5 cm and infiltrating ductal carcinoma was the most common pathology (92.9%). As for pharmacological therapy, the most commonly used regimens were Chemotherapy + Trastuzumab combination (79.1%) in neoadjuvant setting, Hormonotherapy alone (56.2%) in adjuvant setting, and Chemotherapy + Targeted therapy combination (64.8%) as palliative treatment. At the last patient evaluation, 36.9% had complete response, while 33.2% had progressive disease. Median overall survival (OS) and progression-free survival (PFS) were not reached in patients on neoadjuvant/adjuvant pharmacotherapy. As for patients on palliative intent pharmacotherapy, median OS and PFS were 64.7 and 29.3 months respectively. Conclusion This study provided updated figures regarding HER2 overexpression in BC in Saudi Arabia: HER2 overexpression rate (29.9%) was within the range reported in previous studies. Patients' demographic and clinical characteristics were also similar to those reported earlier, with a median age at diagnosis of 46 years and one third of patients having locally advanced/metastatic disease at diagnosis.